Testicular appendix (hydatid of Morgagni) torsion in adult urological management: evaluation of treatment outcomes - I. S. Shormanov; D. N. Shedrov; D. Y. Garova; A. I. Ryzhkov (Вестник урологии, 2023)
Introduction. Testicular appendix (hydatid of Morgagni) torsion (TAT) is relatively rare in patients over 18 years of age. To date, there are no systematised data on the long-term results of TAT treatment depending on the diagnostic and therapeutic tactics undertaken. Accordingly, there are no clear algorithms for the management of such patients.Objective. To evaluate and compare long-term results of various treatment options for patients with testicular appendix torsion over the age of 18 years.Materials & methods. The age of patients is from 18 to 46 years. We analysed the treatment results of TAT-patients in three comparison groups: those who received conservative treatment for uncomplicated course of the disease (group 1, n = 17), early surgical treatment for complicated course (group 2, n = 16), and patients who were operated on for complicated course if conservative therapy was ineffective (group 3, n = 17). The exclusion criteria were concomitant scrotal pathology (hydrocele, funicular hydrocele, varicocele, epididymitis); severe somatic pathology (diabetes mellitus, hypertension, heart attack, stroke). Evaluation of long-term results was carried out 9 – 12 months after the acute episode. Scrotal ultrasound (US) and Doppler US of testicular vessels were compared, endocrine status (levels of total testosterone, luteinising hormone, follicle-stimulating hormone) and reproductive function were studied based on the results of semen analysis and MAR-test.Results. Analyses of long-term clinical data revealed recurrent orchalgia in 29.4% of patients in group 3. Also, in group 3, US revealed testicular asymmetry in 47.1% of patients accompanied by hypotrophy of the affected testis up to 20.8% of the volume compared to the contralateral testis. There were no significant changes and differences in groups 1 and 2. Evaluation of endocrine function showed no significant difference of the studied groups from the control normative indicators. Semen analysis parameters were not significantly changed in groups 1 and 2. In group 3, asthenozoospermia was found in 23.5% of cases, and teratozoospermia was detected in 29.4% of patients.Conclusion. Conservative treatment for TAT without inflammatory changes does not lead to impaired spermatogenesis and structural changes of both the testis and its appendix in the long-term follow-up period and is the most accepted in practice. Early surgical intervention for inflammatory changes shows similar long-term results. Prolonged conservative treatment for TAT in secondary orchoepidididymitis with delayed surgery significantly worsens long-term results. This fact also demonstrates the need for early surgery in complicated TAT.